Analysis of Off-Balance Sheet Activities in Uzbekistan’s Banking Sector - Raimberdieva Zulkhumor daughter of Abdusamad (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
Off-balance sheet activities in commercial banks are based on a complex and challenging field of financial research. This annotation summarizes the main ideas of this field by emphasizing important elements and issues related to understanding off balance sheet dynamics. Off-balance sheet activities are financial operations and commitments made by commercial banks without direct representation on the conventional balance sheet. These activities encompass a variety of financial instruments and transactions, including derivatives contracts, securitization, and contingent liabilities. Risk management, regulatory compliance, and profit optimization typically drive off-balance sheet activities. This comment helps one understand the subtle functions and consequences of off-balance sheet operations. It presents the idea, explores the reasons why banks use such approaches, and emphasizes the importance of these operations in determining a bank's risk exposure and general financial situation. Examining several kinds of off-balance sheet instruments—such as loan promises and standby letters of credit—helps one to grasp the processes used by commercial banks practically. Furthermore, the annotation emphasizes the importance of including off-balance sheet activities in the larger framework of financial analysis and decision-making. For regulators, investors, and bankers, knowledge of the complexity of off-balance sheet activity becomes critical as financial environments change. This annotation is to provide a basic understanding of the topic, therefore enabling a more in-depth study and analysis of the off-balance sheet terrain in commercial banks.